Prevalence of hypertension and its associated risk factors in the rural field practice area of a tertiary care teaching hospital of Coastal Andhra Pradesh, India - Ponnaganti, Satyanarayana Chowdary; Undavalli, Vamsi Krishna; Sayyad, Asha Parveen; Narni, Hanumanth; Muthe, Amarnath (International Journal of Research in Medical Sciences, 2018)
Background: Hypertension is a major public health challenge in present phase of socio-demographic and epidemiological transition leading to various complications causing high mortality and morbidity. This study was carried out to observe changing trends prevalence of hypertension and its association with major risk factors in rural community. Methods: A community based cross sectional study was carried out among 1500 individuals (654 men and 846 women) aged 18-65 years living in villages under rural field practice area of Dr. Pinnamaneni Siddhartha Institute of Medical Sciences and Research Foundation, Chinaoutpally, Krishna district, Andhra Pradesh. Information on socio-demographic data and risk factors was obtained. Height, weight and blood pressure were measured. Results: The mean systolic blood pressure was 130±19mmHg and diastolic blood pressure was 86±11mmHg. The mean age, waist circumference and BMI are 40±13 years, 85±11cm’s and 24±4kg/m2 respectively. The prevalence of hypertension and pre-hypertension in the age group of 18-65 years was reported to be 27.7% and 24.3% respectively. The prevalence of hypertension was significantly higher with increasing age, BMI, positive family history and low physical activity. Conclusions: Hypertension is one of the major public health problems in India with a long preclinical phase i.e. pre hypertension. Sedentary lifestyle, obesity and tobacco consumption are the modifiable risk factors associated with high prevalence of hypertension. These observations re-emphasize the need to follow effective preventive interventions such as healthy life style with regular physical activity and healthy dietary practices to be adopted to prevent hypertension.